Sensitivity Consequences of Ethylene in Determining the Vase Life of Eremurus spectabilis and E. persicus - Somaye Sayed Mahmoudian; Nematollah Etemadi; Rahim Amirikhah; Shadab Panahi (Horticulturae, 2023)
Foxtail lily (Eremurus), as a medicinal-ornamental geophyte, has recently emerged in the cut flower market as a novel, commercially significant specialty cut flower (SCF). However, there is limited information about the sensitivity to ethylene of foxtail lily species for managing the ethylene-mediated senescence to prolong the vase life and maintain the ornamental quality of this flower. The purpose of the current study was to compare the ethylene production rates and patterns, as well as the responses to exogenous ethylene and ethylene inhibitors, between two species, E. spectabilis and E. persicus, to better understand the role of ethylene in Eremurus inflorescence senescence. The results revealed that exogenous ethylene (10 μL L−1), as a pulsing or continuous method, dramatically accelerated petal wilting in E. spectabilis and petal abscission in E. persicus. Furthermore, the rate and patterns of endogenous ethylene production varied significantly among the two investigated species. Interestingly, E. persicus exhibited a higher rate of ethylene production than E. spectabilis on the first day after harvesting, but the reverse was true at the end of the vase life (Day 4 of the vase period). The results revealed that the treatments with ethylene inhibitors considerably improved the water relations and vase longevity of both foxtail lily species. The vase life of E. spectabilis was dramatically enhanced by silver thiosulfate complex (STS) treatment (0.2 mM pulse for 24 h) from 5 d (control) to 7 d. Furthermore, 1-methylcyclopropene (1-MCP) at 0.5 and 1.0 μL L−1 markedly improved water uptake, relative fresh weight, and water balance and extended the vase life of cut inflorescences by ~2 d in E. spectabilis and E. persicus, compared with those of control cut inflorescences, respectively. This research revealed that ethylene is involved in controlling the senescence of foxtail lily flowers, and two tested species exhibited distinct forms of ethylene sensitivity, including abscission type in E. persicus and wilting-type in E. spectabilis. Collectively, these findings suggest that ethylene is involved in the senescence of cut foxtail lily inflorescence and that ethylene inhibitors can prolong vase life.